2023
DOI: 10.2215/cjn.0000000000000019
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin, Concomitant Prescription of Opioids, and Benzodiazepines among Kidney Transplant Recipients

Abstract: Background Gabapentinoids, commonly used for treating neuropathic pain, may be misused and coprescribed with opioid and benzodiazepine, increasing the risk of mortality and dependency among kidney transplant recipients.Methods We identified adult kidney transplant recipients who enrolled in Medicare Part D in 2006-2017 using the United States Renal Data System/Medicare claims database. We characterized recipients' post-transplant concomitant prescription of gabapentinoids, opioids, and benzodiazepine stratifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“… 4 In addition, kidney donation may be associated with long-term disease and pain. 12 , 13 Inadequate treatment of postoperative pain can reduce the patient’s ability to participate in rehabilitation plans, leading to poor postoperative outcomes, and delaying patient recovery and discharge time, reducing quality of life and satisfaction, increasing resource consumption and medical costs. PSQ is a non-invasive method for measuring pain sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“… 4 In addition, kidney donation may be associated with long-term disease and pain. 12 , 13 Inadequate treatment of postoperative pain can reduce the patient’s ability to participate in rehabilitation plans, leading to poor postoperative outcomes, and delaying patient recovery and discharge time, reducing quality of life and satisfaction, increasing resource consumption and medical costs. PSQ is a non-invasive method for measuring pain sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of CJASN , Chen et al 5 present results of an observational study using national registry data from the United States Renal Data System (USRDS), demonstrating new evidence that gabapentinoids are associated with a higher risk of death among kidney transplant recipients. The authors identified adults who had a first-time kidney transplant between 2006 and 2017 and were enrolled in Medicare Part D and Medicare as the primary insurer at time of transplant.…”
mentioning
confidence: 99%
“…10,11 In summary, the work of Chen et al using rigorous observational methods brings important attention to the allcause mortality risk of gabapentinoids, especially in combination with opioids and benzodiazepines, among kidney transplant recipients. 5 Future work building off these findings to explore mechanisms, mediators, and moderators is warranted. This study brings ever more urgency to developing effective nonpharmacologic pain treatment options and risky pharmacotherapy deimplementation strategies in this vulnerable population.…”
mentioning
confidence: 99%